If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -127 = 3x + 76 Reorder the terms: -127 + 10x = 3x + 76 Reorder the terms: -127 + 10x = 76 + 3x Solving -127 + 10x = 76 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -127 + 10x + -3x = 76 + 3x + -3x Combine like terms: 10x + -3x = 7x -127 + 7x = 76 + 3x + -3x Combine like terms: 3x + -3x = 0 -127 + 7x = 76 + 0 -127 + 7x = 76 Add '127' to each side of the equation. -127 + 127 + 7x = 76 + 127 Combine like terms: -127 + 127 = 0 0 + 7x = 76 + 127 7x = 76 + 127 Combine like terms: 76 + 127 = 203 7x = 203 Divide each side by '7'. x = 29 Simplifying x = 29
| (-2h^2/9)^3 | | 22-a=7 | | 2k+22=-6(-k-2)+2 | | -2v-30=-7(v-5) | | 18t+-8=1 | | 32+2x=90 | | 56-2u=25 | | 0=8t^2-5t-13 | | -10-7y=-90 | | 100/x)·X=(28/21)·X | | G(12)=9 | | -7u+4(u-8)=-26 | | t^-5/2-32=0 | | 7x+9=13x-29 | | F(12)=9 | | -0.2x^2+0.4x+0.2=0 | | (q-5)*8=64 | | 2x(13-4)-(23/23) | | 21-2x=12 | | -4(x-6)=-6x+36 | | T^-5/2=32 | | 0=16*t^2 | | -4(x-6)=-6(-k-2)+2 | | -51+3x=9x+57 | | F+9=c | | [3x-5]= | | 2y^4-50y^2=0 | | 3x+3+5x+2=21 | | 256=16*t^2 | | -138-9x=x+122 | | G=-9+100 | | 38-6x=6-10 |